The Role of Islamic Religious Education Teachers in Optimizing Competency-Based Curriculum Implementation - Mohammad Riza Zainuddin (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2017)
The curriculum is an important thing in the world of education, without an educational curriculum will run unbalanced. Competency-based curriculum is an effort in improving the quality of education quality, this is what causes a problem and adjustment of PAI Teachers in teaching and learning process. The existence of the optimal application is done by Islamic Religious Education Teachers by seeking various preparations, methods and other efforts as mentioned above, as well as cooperation among teachers, both Islamic Religious Education Teachers and Counseling Guidance and general teachers. Therefore, efforts are made more on the increase again that the madrasah especially Islamic Religious Education Teachers improve again its cooperation with parents and more students execute themselves with other teachers, especially Teacher Counseling to monitor the problems and development of students.